REPRESENTATION OF BEAUTY ON INDONESIAN TEENAGERS’ TELEVISION DRAMA SERIES - Hendriyani Hendriyani; B Guntarto (The Indonesian Journal of Communication Studies, 2015)
This study explores ideal beauty concept represented in the teenagers’ television drama series in Indonesia. Analyzing the female characters of drama series that were broadcast in 2010-201 as a pilot study, this research finds that certain body images dominate the television screens: majority of actors are thin, young, have fair skin and long hair. Most of them are portrayed as super feminin girls. Actors with Western Indonesian features are consisted of majority of drama population, followed by Eastern Asian and Caucasian, while the Eastern Indonesians are underservised. Brain is not a prominent feature, but kindness is highly appreciated. This study tried to develop a framework for analyzing teenagers’ television drama that can be applied to a larger sample of programs or other television genre.